Are socio-economic inequalities related to cardiovascular disease risk? A systematic review and meta-analysis of prospective studies - Ololade J. Baruwa; Federica Alberti; Sunday Onagbiye; Annalisa Guddemi; Anna Odone; Hannah Ricci; Maddalena Gaeta; Schmid Daniela; Cristian Ricci (BMC Cardiovascular Disorders)
Abstract Purpose The aim of this research was to investigate the relationship between socio-economic inequalities and fatal and non-fatal cardiovascular events. Methods A systematic review of recently published cohort studies and a meta-analysis of relative risk (RR) of low compared with high socio-economic status (SES) in relation to cardiovascular incidence and mortality was conducted. Supplementary evaluations were conducted considering different proxies of SES in relation to different types of cardiovascular disease (CVD). Results We identified 17 studies including approximately 26.5 million of participants with more than 900,000 CVD events. We estimated a 50% increased CVD risk for low SES with respect to high SES (RR = 1.49 [95% confidence interval: 1.26, 1.78]). For sex-specific risk, we estimated a 79% increased CVD risk for women of low SES (RR = 1.79 [1.30, 2.46]). In men, the same investigation found a 45% increased CVD risk (RR = 1.45 [1.09, 1.92]). We reported that low education (RR = 1.56 [1.27, 1.91]), increased CVD risk the most, more than low income (RR = 1.38 [1.12, 1.70]). Conclusion Although not statistically significant, women of low SES were at higher CVD risk than men. CVD risk was more relevant to educational inequality than economic inequality.